Effect of Exhaust- and Nonexhaust-Related Components of Particulate Matter on Long-Term Survival After Stroke. Issue 12 (December 2016) - Desikan, Anita; Crichton, Siobhan; Hoang, Uy; Barratt, Benjamin; Beevers, Sean D.; Kelly, Frank J.; Wolfe, Charles D.A.
Abstract : Background and Purpose—: Outdoor air pollution represents a potentially modifiable risk factor for stroke. We examined the link between ambient pollution and mortality up to 5 years poststroke, especially for pollutants associated with vehicle exhaust. Methods—: Data from the South London Stroke Register, a population-based register covering an urban, multiethnic population, were used. Hazard ratios (HR) for a 1 interquartile range increase in particulate matter <2.5 µm diameter (PM2.5 ) and PM <10 µm (PM10 ) were estimated poststroke using Cox regression, overall and broken down into exhaust and nonexhaust components. Analysis was stratified for ischemic and hemorrhagic strokes and was further broken down by Oxford Community Stroke Project classification. Results—: The hazard of death associated with PM2.5 up to 5 years after stroke was significantly elevated ( P =0.006) for all strokes (HR=1.28; 95% confidence interval [CI], 1.08–1.53) and ischemic strokes (HR, 1.32; 95% CI, 1.08–1.62). Within ischemic subtypes, PM2.5 pollution increased mortality risk for total anterior circulation infarcts by 2-fold (HR, 2.01; 95% CI, 1.17–3.48; P =0.012) and by 78% for lacunar infarcts (HR, 1.78; 95% CI, 1.18–2.66; P =0.006). PM10 pollution was associated with 45% increased mortality risk for lacunar infarct strokes (HR, 1.45; 95% CI, 1.06–2.00; P =0.022). Separating PM2.5 and PM10 into exhaust and nonexhaust components did not show increased mortality. Conclusions—: Exposure to certain outdoor PM pollution, particularly PM2.5, increased mortality risk poststroke up to 5 years after the initial stroke.